The role of tourism marketing in the development of tourist regions - Islam, Telli Mohamed (The International tax journal, 2026)
The objective of this study is to analyze the importance of the dimensions of the tourism product in the development of the tourist regions. The statistical analysis of the main compounds (ACP) and the hierarchical cluster analysis were used. The researcher aims to use the method of analysis in the main vehicles, which aims to study all the available variables represented by tourist elements that are rich in Algeria, which affect the development potential. Four tourist attractions were summarized as follows: Tourism infrastructure, Natural and ecological factors) as the use of multi linear regression analysis to identify and evaluate the model between tourist attractions and tourist nights. It was found that the first factor and the second most influential factor. The study also uses the cluster analysis method to collect the country's mandates in regional development groups, namely, tourism division, tourism sector adaptation, and the consolidation of states in four regions with homogeneity and tourist variation.